Investigation of phosphate adsorption by a polyethersulfone-type affinity membrane using experimental and DFT methods. Issue 52 (7th November 2016) - Wang, Xiuli; Song, Laizhou; Yang, Feifei; He, Jun
Abstract: A fabricated polyethersulfone (PES)-type affinity membrane was employed for the removal of phosphate from the aqueous solution. Influences of pH, contact time, temperature, and initial phosphate concentration, as well as the coexistent Cl −, , Ca(II), and Mg(II) on the phosphate adsorption were evaluated. The adsorption kinetics and the adsorption isotherms of this membrane toward phosphate were investigated. In addition, the insight into the phosphate uptake at an atomic-scale was revealed by the density functional theory calculations. The coexistent Cl – and showed a disturbance on the uptake of phosphate; conversely, the presence of Ca(II) and Mg(II) increased the uptake of phosphate. The negative influence of was more remarkable than that of Cl – due to the notably nucleophilic nature of this anion. The accelerating role of Ca(II) was stronger than that of Mg(II), because the Ca(II)-loaded membrane exhibited a more stronger affinity to phosphate than the Mg(II)-loaded form. Lagergren second-order and Langmuir models were suitable for describing the adsorption kinetics and adsorption isotherms, and the phosphate adsorption onto the membrane was a spontaneous and endothermic process.